Self-powered PEDOT and derivate monoelectrodes to harvest rain energy. (November 2017) - Wang, Yingli; Duan, Jialong; Zhao, Yuanyuan; Duan, Yanyan; Tang, Qunwei
Abstract: Self-powered electrodes for harvesting clean energy from nature is a promising solution to meet specific requirements of multi-purpose applications. In the current work, a category of self-powered monoelectrodes are made from poly(3, 4-ethylenedioxythiophene) (PEDOT), PEDOT-graphene complex and PEDOT-graphene/PtCo to harvest rain energy. Arising from charging/discharging processes of electron/cation pesudo-capacitances at monoelectrode/rain interfaces, the self-powered monoelectrodes yield maximized current of 4.41 μA/droplet and voltage of 136.66 μV/droplet. By enriching electrons at these self-powered monoelectrodes, the electricity outputs can be further enhanced. The reasonable electrical signals and good durability extend our knowledge to advanced rain energy harvesting platforms. By further increasing power outputs, these self-powered monoelectrodes are promising for potential applications in rain enriched regions. Graphical abstract: Self-powered monoelectrodes from PEDOT derivates are made to harvest rain energy, yielding maximized current of 4.41 μA/drop and voltage 136.66 μV/drop. The successful realization of physical proof-of-concept monoelectrodes demonstrates a promising revenue of harvesting rain energy. Highlights: Self-powered monoelectrodes from PEDOT and derivates are made to harvest rain energy. High electron concentration promotes electricity outputs. PEDOT-graphene/PtCo monoelectrode can harvest maximized rain energy.